2017
DOI: 10.3389/fpsyg.2017.00382
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Investigation of the Role of Openness in Relationship Quality among Emerging Adult Chinese Couples

Abstract: This study tested emerging adult couples’ openness and its fit effect on their romantic relationship quality using quadratic polynomial regression and response surface analysis. Participants were 260 emerging adult dyads. Both dyads’ openness and relationship quality were measured. The result showed that (1) female and male openness contribute differently to relationship quality; (2) couples with similar high openness could experience better relationship quality than those with similar low openness traits; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 76 publications
0
9
0
1
Order By: Relevance
“…Thus, complementary openness could help enhance couples' satisfaction levels. Zhou et al ( 2017 ) found that, for Chinese dating young adults, openness in complementary matching dyads corresponds to better relationship quality than openness in moderate matching dyads.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, complementary openness could help enhance couples' satisfaction levels. Zhou et al ( 2017 ) found that, for Chinese dating young adults, openness in complementary matching dyads corresponds to better relationship quality than openness in moderate matching dyads.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on similarity have assumed linear effects, thereby neglecting the possibilities (a) that too much similarity might be as detrimental for relationship outcomes as too much dissimilarity and (b) that similarity on the low end of a trait dimension has different effects on the relationship as compared to similarity on the high end pole. Indeed, in two recent studies (Weidmann, Schönbrodt, Ledermann, & Grob, 2017;Zhou, Wang, Chen, Zhang, & Zhou, 2017) it was shown that the association between similarity and relationship satisfaction is more complex than previously thought. For instance, in a study with 237 couples, Weidmann et al (2017) observed that couples in which both members had moderate levels of openness were more satisfied with their relationships two years later than couples whose members had similar high or low levels of openness or were dissimilar to each other.…”
Section: Personality and Partner Selectionmentioning
confidence: 98%
“…In this way, dyadic response surface analysis provides a nuanced view on partner (dis)similarity and relationship satisfaction (Schönbrodt et al 2018). This method has already been applied to investigate the association between the Big Five personality traits and several aspects of relationship quality (Leikas et al 2018;van Scheppingen et al 2019;Weidmann et al 2017;Zhou et al 2017). In a study with 141 couples, for example, Weidmann et al (2017) found relationship satisfaction of men to be particularly high when the men and their spouses were either congruently low or congruently high in neuroticism.…”
Section: Similarity In Loneliness and Relationship Satisfactionmentioning
confidence: 99%